Cigarette use among the 16 to 20 years school Students of rural area of Navatkulli, Jaffna - Miraaj, R.; Miraaj, V. (Wayamba University of Sri Lanka Kuliyapitiya Sri Lanka, 2018)
A cigarette is a narrow cylinder of finely cut tobacco leaves that are rolled into thin paper for smoking. The cigarette is ignited at one end, causing the cigarette to smolder and allowing smoke to be inhaled from the other end. Cigarette manufacturers have described cigarette as a drug administration system for the delivery of nicotine in acceptable and attractive form. Cigarette are addictive (because of nicotine) and cause cancer, heart problems, and other health problems. In 2015, over 1.1 billion people smoked tobacco. Far more males than females smoked tobacco. Although it is declining worldwide and in many countries, the prevalence of tobacco smoking appears to be increasing in the WHO Eastern Mediterranean region and the African region. This cross sectional study is about the cigarette use among the male school students between the ages of 16-20 year at rural area of Navatkuli, Jaffna between Octobers to December 2017. This study was undertaken to determine the prevalence and age initiation of cigarette use among school students in rural area of Navatkuli, Jaffna. The study included 100 male students of Navatkuli area and the data was collected by researchers through a self- administered questionnaire. A total of 100 male students between the ages of 16-20 year were included for this study. Here 29(29%) cigarette used students were screened and 16 years is the age initiation of cigarette use among school students. Here the prevalence of cigarette usage to be increased with their age. 20 years students have the high smoking habit than other ages. Parent's behavior, social pressure, their environment & friends are found to be the most common causes of initiating and addicting cigarette usage of students.
Keywords: Cigarette; Navatkuli; Rural area